Pre-treatment and anaerobic codigestion of waste activated sludge from a petrochemical wastewater treatment plant - van der Merwe, Carla (Centre for Bioprocess Engineering Research, 2023)
During the aerobic treatment of wastewater, waste activated sludge (WAS) is generated which requires further treatment. The typical treatment method applied for treating the sludge is incineration. The National Environmental Management: Air Quality Act (NEM:AQA), promulgated in 2004, was amended in 2013 to include the list of activities which result in atmospheric emissions. One of the activities included in the list is the specification of the minimum emission standards (MES) for thermal treatment of hazardous waste; this includes the incineration of waste activated sludge. Alternative treatment methods should be considered to minimise emissions and to derive some benefit from the WAS. One such potential method is the pre-treatment of waste activated sludge combined with co-digestion in an anaerobic digester. This study focusses on selection of a feasible pre-treatment option for the anaerobic digestion of waste activated sludge produced in a petrochemical wastewater treatment plant (PWWTP) to improve its subsequent anaerobic digestion. Following pre-treatment, the study specifically focusses on digestion of the pre-treated sludge in an attached-growth down-flow anaerobic digester with co-digestion with an available wastewater stream containing soluble organic material. This stream will be referred to as the soluble wastewater stream (SWWS). The WAS stream is dewatered in the PWWTP to reduce the volume of the stream for treatment. The test work was done on both the “as-processed” waste activated sludge originating from the bottom of the settlers as well as the dewatered stream. The “as processed” WAS stream (which is referred to as 1 wt% WAS) has a solids concentration which could vary between 9 000 mg/L to 15 000 mg/L. The total chemical oxygen demand (TCOD) of the stream ranged from 18 000 mg/L to 25 000 mg/L, whereas the soluble chemical oxygen demand (SCOD) was measured to range between 160 mg/L to 200 mg/L. Most of the COD was contained in the sludge floc and would not be freely available for the anaerobic micro-organisms to digest. The dewatered WAS (which is referred to as 10 wt% WAS) solids concentration would vary between 90 000 mg/L to 120 000 mg/L. Due to the removal of water in the dewatering step, the TCOD would increase to between 160 000 mg/L to 180 000 mg/L, however the SCOD remained low at 160 mg/L to 200 mg/L. To anaerobically digest both these streams “as is” would be challenging and require very long retention time and large digesters, yielding low conversion into biogas. Pre-treatment options are available to lyse the cell walls of the WAS, increasing the SCOD, which could make anaerobic digestion of WAS technically feasible. The research identified thermal, chemical and thermo-chemical pre-treatment processes as feasible options for the production facility to consider. Thermal pre-treatment was done at 60, 70, 80, 100, 120 and 133°C for the 1 wt% WAS and 10 wt% WAS. It was observed that the % soluble COD increased from the baseline of 2% to 24% at 133°C which supported the findings of many researchers, stating that the degree of cell disruption improves with an increase in temperature. Chemical pre-treatment with sodium hydroxide was done at 0.2, 0.6 and 1.0 ml 48% NaOH/g solids. The fraction of soluble COD was increased to as high as 27%. Less sodium hydroxide per gram solids was required for the dewatered waste activated sludge than for the 1 wt% WAS. It was found that thermo-chemical pre-treatment of the 10 wt% WAS at 133°C with 0.3 ml 48% NaOH/g solids would improve the fraction of soluble COD to greater than 80%. The treated waste activated sludge was then co-digested in a pilot scale supporting-growth down-flow anaerobic digester to evaluate the conversion of the organics and the quantity and quality of the biogas formed. The stream used for the co-digestion was a soluble wastewater stream which contains mostly volatile fatty acids (VFA) with acetic acid as the major component. The SCOD of the SWWS would range between 12 000 mg/L to 20 000 mg/L. The volumetric ratio of the lysed WAS and SWWS streams tested were 1:20, 1:25 and 1:30 to determine which ratio would provide the required outlet specifications from the anaerobic digester, set at an effluent COD concentration of less than 3 000 mg/L and effluent suspended solids of less than 3 000 mg/L. These specifications are set based on downstream process requirements. The optimum ratio of the lysed waste activated sludge to soluble wastewater (SWWS) was 1:30 for this specific production facility to meet their effluent specifications. The COD conversion for co-digestion was 87.2 ± 0.3% and the percentage suspended solids converted in the anaerobic digester was estimated to be 57.7 ± 5.2%. The system was designed for a methane fraction of 50% as the theoretical methane fraction for acetic acid is 51%. When co-digesting the WAS with the SWWS, the methane fraction increased to 57.38 ± 2.95%. An increase in the methane fraction was expected when co-digesting the WAS with the SWWS. The theoretical methane yield for the process conditions are 0.438 l CH4/g COD converted. Based on the measured flow rates and methane analysis, the methane yield was 0.38 ± 0.02 l CH4/g COD converted, equivalent to 87% of theoretical yield. This difference could be due to biogas flow meter inaccuracy, and variation in methane fraction. A block flow diagram was developed for the proposed process solution and the main pieces of equipment sized and equipment costs estimated. This was done for a system with and without a dewatering step. The system with a dewatering step had lower capital expenditure as well as lower operating expenditure. The amount of biogas generated was sufficient to be used in a combined heat and power system to generate the steam required for the pre-treatment and sufficient electricity for the pumps used in the pre-treatment system. Thermo-chemical pre-treatment of dewatered WAS (concentrated to 10 wt% solids) from a petrochemical wastewater treatment plant combined with co-digestion of the lysed WAS with a VFA-rich stream is a technically feasible option for the treatment of WAS. This solution reduces the amount of WAS sent to the incinerator which, in turn, will improve the emissions footprint with regards to particulate matter, NOx, SOx, metals, dioxins and furan emissions. Co-digestion would also result in the WAS stream being used to generate a biogas which supports the sustainable development agenda, therefore moving up in the waste hierarchy.